How to Read a Paper / The Basic of Evidence-Based Medicine: Fifth Edition - Greenhalgh Trisha (Wiley, 2014)
This book is an introduction to evidence-based Medicine. Preface, Acknowledgements, Why Read Papers at All?, Searching the Literature, Getting your Bearings: What is This Paper About, Assessing Methodological Quality, Statistics for the Non-Statistician, Papers that Report Trials of Drug Treatments and Other Simple Interventions, Papers that Report Trials of Complex Interventions, Papers that Report Diagnostic or Screening Tests, Papers that Summarize Other Papers (Systematic Reviews and Meta-Analyses), Papers that Tell You What to Do (Guidelines), Papers that Tell you What Things Cost (Economic Analyses), Papers that Go Beyond Numbers (Qualitative Research), Papers that Report Questionnaire Research, Papers that Report Quality Improvement Case Studies, Getting Evidence into Practice, Applying Evidence with Patients, Criticisms of Evidence-Based Medicine, Appendices, Index.